Influência do lodo de ETE na massa para fabricação de cerâmica vermelha - Araújo, Franciolli da Silva Dantas de (2008)
The WTP produce many kinds of residue on your treatment stages, but the sludge is the more problematic from the final disposition point view. The actual rate of residue production deriving from technological evolution and the crescent population needs prevents the subtle equilibrium generation between consumption and recycling/reuse, creating problems of pollution resulting from inappropriate management of residues. Thus, is necessary achieve a new equilibrium between the grow from raw materials and energy and the residue generation. This equilibrium should be achieved by technical and economic feasibility of environmental supported models through recycling and reuse. The red ceramic industry stand out in residue absorption question as raw material due their clay mass heterogeneity, constituted by clay minerals and non-clay minerals with wide mineralogical variation, allowing residue inclusion which act like plastic or non-plastic materials, contributing to retain heavy metals contained in residues in the vitreous mass formed during the burning of the ceramic bodies. This work propose the study of the influence of incorporation of 25 wt.% sludge from wastewater treatment plant, according preliminary results, in the mass to produce ceramic bodies. The raw materials was characterized through chemical composition analyses by XRF, mineralogical analyses by XRD, thermal analyses by TG and DTA, Atterberg limits and thermodilatometry. Subsequently was composed the mass with 75 wt.% of clay and 25 wt.% of dried wastewater sludge from UFRN WWTP. Samples with 6,0 x 2,0 x 0,5 cm was produced with unidirectional compacting under pressure of 20MPa and burned in temperatures between 950 and 1,200ºC. After fired, the ceramic bodies have been submitted to physical and mechanical analyses through the measure of firing shrinkage, water absorption, density, apparent porosity and flexural strength; crystallographic analyses through XRD and microstructure analyses by SEM. The technological properties obtained was satisfactory to production of roof tiles with 25 wt.% at 1,200 ºC, but the production of others products at lower temperatures was not feasible